2022
DOI: 10.1021/acsomega.2c00636
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic and Quantum Chemical Investigation of the Pyridine-Borane Complex and the Effects of Dative Bonding on the Normal Modes of Pyridine

Abstract: The pyridine-borane (PyBH 3 ) complex was analyzed by Raman vibrational spectroscopy and density functional theory to elucidate its structural and vibrational properties and to compare these with those for neat pyridine (Py). The borane–nitrogen (BN) bond length, the BN dative bond stretching frequency, and the effects of dative-bonded complex formation on Py are presented. Rather than having a single isolated stretching motion, the complex exhibits multiple BN dative bond stretches that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Nitrogen-containing heterocycles have received much attention in the past as participants in covalent and noncovalent charge transfer interactions. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Additionally, these studies highlight the usefulness of vibrational spectroscopy, particularly Raman spectroscopy, as a probe of noncovalent interactions. Azines and their derivatives have also been studied in halogen-bonded complexes in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-containing heterocycles have received much attention in the past as participants in covalent and noncovalent charge transfer interactions. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Additionally, these studies highlight the usefulness of vibrational spectroscopy, particularly Raman spectroscopy, as a probe of noncovalent interactions. Azines and their derivatives have also been studied in halogen-bonded complexes in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Upon interaction with a Lewis acid, many ligand bands experience a considerable blue-shift. In Raman spectroscopy, the intense band of the ring breathing mode of pyridine experiences a larger blue-shift with stronger interactions of pyridine with a Lewis acid due to greater charge transfer from the nitrogen lone pair to the Lewis acid site. Previous quantum chemical studies on pyridine suggested that the origin of the blue-shift of the ring breathing mode upon interaction with a Lewis acid is due to significant changes in σ electron density accompanied by polarization of the π electron density toward the nitrogen atom. , This polarization of electron density is thought to result in stronger ionic attraction between the nitrogen and the bonded carbon atoms, increasing the frequency of the vibrational mode. Calculations also suggested that the high-frequency shift of the ring breathing mode may also be caused by coupling with in-plane C–H bending modes .…”
Section: Resultsmentioning
confidence: 99%
“…Geometry optimization and Raman vibrational frequencies and optical tensors were calculated using density functional theory with the Minnesota 06 functional M06-2X and the Pople split-valence double-ζ 6-31G** basis set. M06-2X is a global hybrid functional parametrized for nonmetals and excels in predicting noncovalent interactions; [54][55][56][57] 6-31G** features 6 primitive Gaussians with valence orbitals composed of two different basis functions for each: one with a linear combination of three Gaussian functions and the second with one Gaussian function. [58] Self-consistent reaction field (SCRF) [59] calculations were carried out via the integral equation formulism for the polarizable continuum model (IEFPCM) [60][61][62] at the same level of theory in order to compare Raman intensities.…”
Section: Methodsmentioning
confidence: 99%